(untitled) (Academia Journal of Medicine, 2019)
Background: Blood such as VLDL, intermediate density lipoprotein (IDL), chylomicrons, chylomicron remnants and lipoprotein and therefore provides a more accurate estimate of CV risk than LDL-C alone, as shown in numerous epidemiological and clinical studies. This is particularly true for patients who are already on statin therapy or those with elevated levels of VLDL-C such a patients with obesity, metabolic syndrome and diabetes. Subjects and Methods: A pre-structural proforma was used to collect baseline date detailed clinical history with clinical examination and relevant investigation was done on participating individuals. Results: Significant correlation between HbA1c and various circulating lipid parameters and significant difference of lipid parameters in two groups (</.0% and >7.0%) of glycated haemoglobin indicates that HbA1c can be used as a potential biomarker for predicting dyslipidemia in type 2 diabetic patients. Conclusion: As good control of diabetes is shown to keep the lipid levels in near normal range, it appears important to aim at critical control of DM to prevent or at least postpone the onset of various complications.